Correlation of IQ and multiple intelligence on educational psychology learning outcomes - Henik Nur Indahsari; Ratnasari, Dwi; Mustamid, Mustamid (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2025)
This study aims to analyze the relationship between the level of IQ (Intelligence Quotient) and the dominance of Multiple Intelligence on student learning outcomes in educational psychology courses at the PGSD department of UNU Yogyakarta. Using a quantitative approach with a correlational design, this study involved 46 students using simple random sampling technique. Data were collected through questionnaires measuring IQ variables, multiple intelligences, and learning outcomes. The results of the analysis using the Pearson correlation test show that there is a positive and significant relationship between IQ and learning outcomes, with a correlation value of 0.873 (87.3%), which indicates that the higher the IQ score, the higher the learning outcomes obtained by students. The normality test shows that the residual data meets the assumption of normality with an Asymp. Sig. (2-tailed) of 0.126, which is greater than 0.05, indicating that the regression model used is valid. This study confirms that IQ serves as an important predictor of academic success, and an understanding of multiple intelligences can help in designing more effective learning strategies. The implications of this study show the importance of an inclusive educational approach, which considers different types of intelligence to support students' holistic development. This research is expected to provide insights for educators in creating learning environments that are more adaptive and responsive to students' needs.